PENGARUH KEPEMIMPINAN, IKLIM ORGANISASI DAN MOTIVASI BERPRESTASI TERHADAP KINERJA KARYAWAN PT. BINTANG MANDIRI FINANCE JAWA BARAT - Rosmita Rosmita; Kaman Nainggolan (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2015)
Abstract - This study aims to analyze the contribution of Leadership Behavior, Organizational Environment and Achievement Motivation on Employee Performance. The study was conducted at PT Mandiri Star Finance (Limited) branch office in West Java, with a population of 186 people. Researchers selected 128 sampe by using random sampling method. The  research  found  out  that  there  is  a  positive  effect  of  the contribution  of  leadership behavior, and achievement motivation on employee performance, while the organizational climate has a negative effect on the performance of employees, and therefore was excluded from the model.The leadership  behavior  and achievement  motivation  are important  factors that  must  be  improved to increase employee performanceKeywords: Behavioral Leadership, Achievement Motivation, Employee Performance